2014
DOI: 10.1002/bio.2730
|View full text |Cite
|
Sign up to set email alerts
|

Validated spectrofluorimetric and spectrophotometric methods for the determination of brimonidine tartrate in ophthalmic solutions via derivatization with NBD‐Cl. Application to stability study

Abstract: Two simple, selective and accurate methods were developed and validated for the determination of brimonidine tartrate (BT) in pure state and pharmaceutical formulations. Both methods are based on the coupling of the drug with 4-chloro-7-nitro-2,1,3-benzoxadiazole in borate buffer (pH 8.5) at 70 °C and measurement of the reaction product spectrophotometrically at 407 nm (method I) or spectrofluorimetrically at 528 nm upon excitation at 460 nm (method II). The calibration graphs were rectilinear over the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The detector wavelength was fixed at 246 nm and the peak areas were integrated automatically using the Hewlett–Packard ChemStation software program [16]. Other apparatus included an ultrasound generator and a SevenEasy pH meter (Mettler Toledo, USA) that was equipped with a combined glass–calomel electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detector wavelength was fixed at 246 nm and the peak areas were integrated automatically using the Hewlett–Packard ChemStation software program [16]. Other apparatus included an ultrasound generator and a SevenEasy pH meter (Mettler Toledo, USA) that was equipped with a combined glass–calomel electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Various analytical methods have been reported for the determination of brimonidine tartrate, including electroanalytical method [14, 15], spectrophotometric method [16], highly sensitive gas chromatography/mass spectrometric assay [17], high-performance thin layer chromatography (HPTLC) [18], high-performance liquid chromatography (HPLC) [1921], liquid chromatography–mass spectrometry (LC–MS) [22, 23] and high performance liquid chromatography-tandem mass spectrometry (HPLC-TMS) [24]. However, some of the above-described methods are limited in either low sensitivity or specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey reveals several analytical methods for quantitative estimation of BRD in body fluids and in pharmaceutical formulations by spectrophotometry [4][5][6][7][8][9][10], liquid chromatography [11][12][13][14][15][16][17][18][19][20][21] and electrochemical methods [22][23][24].…”
Section: …………………………………………………………………………………………………… Introductionmentioning
confidence: 99%
“…The literature survey showed that there were many analytical methods for the quantitative analysis of BRI and TIM, e.g. HPLC [5][6][7][8][9][10][11], spectrophotometry [12-14], flourimetric methods [15,16], high-performance thinlayer chromatography [17], capillary electrophoresis [18], gas chromatography-mass spectrometry [19], chemiluminescence method [20], membrane electrodes method [21] and extraction-photometric method [22]. This paper describes new implementations of the sym5-CWT and mexh-CWT methods to the UV absorption spectra for the simultaneous quantification of BRI and TIM in synthetic binary mixtures and commercial ophthalmic samples.…”
Section: Introductionmentioning
confidence: 99%